Karakteristik Prilaku Arah Belok Kendaraan Tossa Hercules Ditinjau Dari Sudut Kemiringan Jalan - Dantes, Kadek Rihendra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Direction of the vehicle stability is influenced by many things, both in terms of design and the operator of the vehicle itself. The emphasis is one of the influential, it is obvious when the vehicle turns, at which time the position of the focus will turn to change the result of the centrifugal force occurs. Position and magnitude of the centrifugal force that occurs will affect the vehicle slip angle, which will affect the performance of the vehicle. To determine the direction of vehicle behavior, use some concepts: understeer, oversteer, and neutral steer and understeer constant index (Kus). In analyzing the stability of the vehicle used by the calculation analysis Quasi-Dynamic calculation method. With the initial condition is referred to as ideal conditions or conditions Akerman (Î±r = Î±f = 0). Outcomes that will result in a critical condition when turning the vehicle with respect to the rear tire slip angle (Î±r) and the front tire slip angle (Î±f) that occurred in order to obtain the vehicle oversteer and understeer conditions.Keywords: rear tire slip angle (Î±r) and the front tire slip angle (Î±f), understeer,